Role of Transnational Companies in Implementaion of the Import Phaseout Strategy in the Agroindustrial Sector - ZOBOV, Alexander M.; DEGTEREVA, Ekaterina A.; CHERNOVA, Veronica Yu.; STAROSTIN, Vasily S.; GOLODOVA, Zhanna G. (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017, 2017)
The objective of this research is to study the theoretical concepts and to develop the recommendations to reveal the possibilities of realization of the import phaseout strategy in the Russian food industry in a competitive environment with the largest transnational corporations. The analysis performed in this branch showed that nowadays the import phaseout should be closely connected to the stimulation of the internal demand and state support of the local manufacturers. It was revealed that the attractiveness of the Russian food industry led to the situation when now a large share of the Russian market is under the impact of the transnational corporations, the activity of which does not allow the agroindustrial complex to develop efficiently. As a solution of this situation, it is offered to create the agricultural cooperatives which can compete with the large transnational companies in the countries with the developed economy.